Perancangan Aplikasi E-Arsip Untuk Efisiensi Pengelolaan Dokumen Di PT XYZ (Showroom dan Bengkel Mobil) - Prianto Roito Siregar; Binastya Anggara Sekti (Prosiding SISFOTEK, 2025)
The rapid development of information technology has encouraged companies to transform toward digitalization, including in document management. PT XYZ, a company engaged in car showroom and workshop services, still relies on conventional archiving systems that lead to several issues, such as difficulties in retrieving documents, risks of losing physical archives, and lack of integration across departments. This study aims to design a web-based e-Archive application to support the document digitalization process, enabling more structured, faster, and efficient archive management. The research method adopts the waterfall model, which includes requirements analysis, system design, prototype implementation using the Next.js framework and MySQL database, and system evaluation. Data were collected through observations of the archiving process at PT XYZ and questionnaires distributed to employees as potential users of the system. The results show that the e-Archive application provides essential features such as digital archive management, fast document retrieval, categorization, and automatic report generation. Based on the questionnaire analysis, most respondents indicated that the application is user-friendly, improves the speed of document retrieval, and enhances work efficiency. In conclusion, the designed e-Archive prototype has proven to minimize the risk of document loss, improve document management, and support data-driven decision-making. The implementation of this application is expected to serve as a strategic step toward sustainable digital archive management at PT XYZ.